Job Market Boom and Gender Tide: The Rise of Canadian Social Sciences in the 20th Century - Warren, Jean-Philippe; Gingras, Yves (Scientia Canadensis, 2007)
AbstractIn the last century, the development of the social sciences in institutions of higher learning has been nothing short of spectacular. This is especially true when considering the period opened by the Second World War, a time when the number of students rose exponentially, faculty body grew accordingly, and the volume of research and publications skyrocketed. Yet a global and quantitative analysis of the evolution of Canadian social sciences is still lacking. If some excellent monographs have contributed to a better knowledge of specific disciplines, Canadian scholars did not produce a global cartography of social sciences' development over the last century. This is precisely what this paper endeavours to provide. Its first section explores the rise in student enrolment (with a special analysis of gender composition), the second looks at the growth of faculty hiring and the third section suggests some hypotheses concerning the spectacular growth of social science disciplines through a discussion of Frank and Gabler's recent book, Reconstructing the University. These sections will provide an introductory global overview of the evolution of social sciences in university-level institutions in Canada. This historical analysis will help us better grasp the changes that affected Canadian social sciences through the last century.